2003
DOI: 10.1016/s0273-1177(02)00731-7
|View full text |Cite
|
Sign up to set email alerts
|

Why is the Hubble flow so quiet?

Abstract: The cosmological vacuum, which is perfectly uniform, dominates by density over all the forms of cosmic matter. It makes the Universe be actually more uniform than it could be seen from the visible picture of the highly non-uniform matter distribution, especially inside the observed cell of uniformity (100 − 150 Mpc). This uniformity reveals itself in the structure of the Hubble matter flow which extends over a giant range of cosmic space scales -from few Mpc to a thousand Mpc,preserving its kinematical identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 20 publications
5
72
0
Order By: Relevance
“…The zero-gravity radius of the Virgo system is about 10 times larger than that of the Local system for which R ZG = 1−1.3 Mpc Chernin et al 2000Chernin et al , 2009. We see here the same factor 10 as for the phase structures of the Virgo and Local systems (Sect.…”
Section: Zero-gravity Radius In the Point-mass Approximationsupporting
confidence: 65%
“…The zero-gravity radius of the Virgo system is about 10 times larger than that of the Local system for which R ZG = 1−1.3 Mpc Chernin et al 2000Chernin et al , 2009. We see here the same factor 10 as for the phase structures of the Virgo and Local systems (Sect.…”
Section: Zero-gravity Radius In the Point-mass Approximationsupporting
confidence: 65%
“…Dark matter antigravity can also affect galaxy motions in our near environment in a volume several Mpc across, as first mentioned by Chernin et al (2000). The region is dominated by our Milky Way and its sister galaxy M 31 at 0.7 Mpc from us, approaching each other with a relative velocity 120 km s −1 .…”
Section: The Very Local Environmentmentioning
confidence: 76%
“…The radical difference in the phase-space structure of the group and the outflow around it is the most prominent feature of the local Hubble cell. We have argued earlier (Chernin et al 2000(Chernin et al , 2006Chernin 2001;Teerikorpi et al 2008) that the physics behind this feature might be due to the interplay between the gravity of the group and antigravity of the dark energy background, so that the group size is less than R v and the flow starts at the distances R > R v (as in the example above). Therefore the zero-gravity surface is located somewhere in the gap between the group and the outflow in the distance interval of 1.2-1.6 Mpc.…”
Section: Zero-gravity Radiusmentioning
confidence: 90%
See 1 more Smart Citation
“…I.D.Karachentsev (Karachentsev & Kashlbadze, 2006;Karachentsev, 2005;Karachentsev et al, 2009;Karachentsev, Karachentseva & Huchtmeier, 2007) and A.D.Chernin (Chernin, Teerikorpi, Baryshev, 2003;Chernin et al, 2007;Chernin et al, 2009;Chernin et al, 2012;Chernin et al, 2013;Chernin et al, 2007;Chernin et al, 2012;Chernin, 2013;Teerikorpi & Chernin, 2010), studying the motions of galaxies in clusters, have shown that anti-gravity effects manifest themselves not only on a cosmic scale, but the scale of clusters of galaxies, for example -the Local Group, including our galaxy (the Milky Way) galaxy Andromeda and dozens of other smaller galaxies. M. Eingorn and A. Zhuk also studied in detail these issues (Brilenkov, Eingorn & Zhuk, 2015;Eingorn & Zhuk, 2012).…”
mentioning
confidence: 99%